Analysis of Students' Concession Understanding Ability in Solving Physics Concepts - Ningsih, Fatma Nurma (Yayasan Nurul Yakin Bunga Tanjung, 2022)
Analysis of Students' Concept Understanding in Solving Physics Problems at SMPN 27 Tanjung Jabung Timur. This research is descriptive quantitative research using a survey design which aims to determine the understanding of the physical concepts of class VII b students on unit quantities and measurements. The research subject was class VII B SMPN 27 Tanjabtim, which involved 20 students. The result data was obtained by giving a concept understanding test in the form of a post-test in the form of multiple choice. The data were analyzed descriptively; the percentage of understanding the concept of each indicator sequentially was 76%, illustrating 73%, classifying 28%, comparing 17%, and explaining 62%. It can be ascertained that the most dominant understanding of physics concepts for class VII b SMPN 27 Tanjabtim is indicators and is in the high category, while the most dominant is in comparison and is in a low category. Factors that cause low student understanding of concepts, namely, lack of interest and motivation of students to repeat the material learned, accustomed to learning by memorizing formulas, not being able to manipulate equations containing three variables and less thorough in understanding questions.